Chromatische Pupillometrie – ein neuer Weg zur funktionellen Glaukomdiagnostik? - Huchzermeyer, Cord (Klinische Monatsblätter für Augenheilkunde, 2023)
Chromatic pupillometry allows quantification of photoreceptor-driven (extrinsic) and melanopsin-driven (intrinsic) responses of the intrinsic-photosensitive retinal ganglion cells (ipRGCs). This small subpopulation of retinal ganglion cells is also affected by glaucoma, making chromatic pupillometry a potential diagnostic tool. Studies show reduced phasic and tonic responses in glaucoma patients. The diagnostic value in earlier studies depended on the technical details and the study design. The purpose of this article is to give an introduction into the principles of chromatic pupillometry and to discuss the potential applications in the management of glaucoma.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Glaukom; Neuroophthalmologie; Pupillometrie; retinale Ganglienzellen